Optimalisasi Pemasaran Madu Trigona Melalui Inovasi Produk Dan Media Digital - Desy Dwi Handayani; Fadila Muajaba Kasanah; Ahmad Dwi Afrizal Putra; Deny Wahyu Tricana (AMMA : Jurnal Pengabdian Masyarakat, 2024)
Mrayan Trigona Park is a place for cultivating trigona honeybees and is used as an educational place. Trigona honey is honey produced by stingless bees. The aim of this research is to identify the obstacles faced by farmers regarding product marketing. Innovations are needed to attract consumer interest and be ready to face competition. This research uses a qualitative approach with observation and interview methods. The results of this research are related to packaging labeling that is more attractive and contains more complete information, innovation in honey flavors, and the creation of social media as a marketing and promotional medium.